Managing the ASEAN economic integration process in the Philippines an assessment of progress in trade liberalization and facilitation - Medalla, Erlinda M. (2012)
This paper is part of the Philippine study for the Mid-Term Review (MTR) of the ASEAN Economic Community (AEC) Blueprint, a project of the Economic Research Institute for ASEAN and East Asia (ERIA). A milestone in ASEAN economic cooperation is the Cebu Declaration on the Acceleration of the Establishment of an ASEAN Community by 2015 during the 12th ASEAN Summit in 2007, and subsequently the passing of the ASEAN Charter. A midterm review of where the member-countries are in moving toward the AEC is thus timely.

At the core of ASEAN integration is the free flow of trade in goods. Accordingly, an essential part of the midterm review is an assessment of progress in the area of trade liberalization and facilitation. Toward this end, two sets of surveys were undertaken: (1) the MTR Questionnaire for Government Officials, and (2) the Firm MTR Survey on Import/Export and Customs Clearance. The questionnaire for government officials gathered information on aspects of ASEAN customs development and integration and the implementation of the national single window and the ASEAN Single Window. The survey of firms provided the view from users, particularly their experiences on the customs clearance and permit release process in other government agencies. This yielded a number of recommendations on the ways forward.
Keywords: ASEAN Countries -- Economic relations; Free trade -- Southeast Asia; Tariff